Impact of early versus late tracheostomy on patient outcomes in a tertiary care multispeciality ICU - Puneet Chopra; Kanwalpreet Sodhi; Anupam Shrivastava; Shivani Tandon; Ramandeep Kaur Joia (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Tracheostomy is a commonly performed procedure in critically ill patients because patients requiring chronic mechanical ventilation (MV) are rising by as much as 5.5% per year. The controversy on likely benefits of early versus late tracheostomy is ongoing. We aimed to study the impact of early versus late tracheostomy on patient outcomes. Material and Methods: A retrospective observational study was performed in intensive care unit (ICU) patients who underwent tracheostomy in a 31-bedded multispeciality ICU of a 350-bedded tertiary care hospital, over a period of 1 year. Data collected included the age, sex, APACHE II score, indication for tracheostomy, timing of procedure, whether surgical or percutaneous, any complication, MV days, ICU stay, and patient outcome. Patients were divided into two groups for statistical comparison: early ≤7 days and late >7 days of MV. Results: A total of 102 patients underwent tracheostomy over the study period, of which 19 were excluded because of inadequate data and exclusion criteria. Of the 83 study patients, 60 had percutaneous, while 23 had surgical tracheostomy. About 51 (61.45%) had early, while 32 (38.55%) had late tracheostomy. On statistical analysis, there was a significant difference in MV days (5 vs 12.5 days, P = 0.002), ICU stay (10 vs 16 days, P = 0.004), mortality (21.6% vs 43.8%, P = 0.032), and decannulation rate (29.41% vs 6.25%, P = 0.009). No difference was observed in hospital stay or complication rates. Conclusion: Early tracheostomy is associated with both morbidity and mortality benefits. Patients requiring MV should be given an option of early tracheostomy.